2009
DOI: 10.1007/s00127-009-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

What do predict anxiety and depression in breast cancer patients? A follow-up study

Abstract: Although the findings indicated that the levels of anxiety and depression decreased over time, a significant number of women had elevated anxiety and depression at the 18 months follow-up. This suggests that all women should be routinely screened for psychological distress and that quality cancer care include processes to treat that 30% of women who have elevated psychological distress. In addition, if breast cancer patients indicated that they are suffering from fatigue or pain, these women who are at particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
171
4
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(211 citation statements)
references
References 34 publications
21
171
4
15
Order By: Relevance
“…Studies examining the prevalence of fatigue among breast cancer patients found that up to 99% of patients suffer from some degree of fatigue during chemotherapy and/or radiotherapy and that more than 60% of them experience moderate to severe fatigue (Bower et al, 2000;2006). Published studies showed that fatigue predicts psychological impairment in the forms of HADS score, depression score and anxiety score (Vahdaninia et al, 2010). Similar results were not found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Studies examining the prevalence of fatigue among breast cancer patients found that up to 99% of patients suffer from some degree of fatigue during chemotherapy and/or radiotherapy and that more than 60% of them experience moderate to severe fatigue (Bower et al, 2000;2006). Published studies showed that fatigue predicts psychological impairment in the forms of HADS score, depression score and anxiety score (Vahdaninia et al, 2010). Similar results were not found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Depression was most frequently associated with fatigue (Bower et al, 2000;Den Oudsten et al, 2009;Vahdaninia et al, 2010) followed by lower income/poor financial status (Eversley et al, 2005;Morrill et al, 2008;Chen et al, 2009), low education (Mehnert and Koch, 2008;Morrill et al, 2008;Alcalar et al, 2012) and younger age (Broeckel et al, 2000;Mehnert and Koch, 2008). Regarding marital status, being unmarried (Broeckel et al, 2000;Morrill et al, 2008), widowed or divorced (Chen et al, 2009) were significantly associated with depression although in contrast with one study which found being married (Pumo et al, 2012) was associated with depression.…”
Section: Factors Associated With Depressionmentioning
confidence: 76%
“…Most of the studies were conducted in USA (thirteen), followed by in Europe (five) and four studies from United Kingdom. Seven studies were conducted in Asian countries (Inagaki et al, 2004;Chen et al, 2009;Karakoyun-Celik et al, 2010;Vahdaninia et al, 2010;Alcalar et al, 2012;Hsiao et al, 2012;Jang et al, 2012). Nineteen of the studies were cross-sectional design and twelve prospective studies.…”
Section: Methods Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar da alta prevalĂȘncia desses sintomas, eles ainda sĂŁo pouco abordados nos serviços de saĂșde 10,11 .…”
Section: Introductionunclassified